Climate-Induced Displacement and Migration Patterns in Bangladesh: A Case Study - Amin, Md. Ruhul (Unisia, 2024)
Climate-induced displacement and migration have become urgent challenges in Bangladesh, a country that is extremely sensitive to the effects of climate change. The patterns and determinants of climate-induced displacement and migration in Bangladesh are investigated in this study, which takes a case study approach. Bangladesh, with a population of over 165 million, is one of the world’s most densely populated countries, and its low-lying terrain makes it especially vulnerable to climate-related disasters, including floods, cyclones, and sea-level rise. According to recent data, between 2008 and 2019, approximately 4.4 million people were displaced annually as a result of natural catastrophes, with climate change accounting for a sizable part. The study uses both quantitative and qualitative approaches, including surveys, interviews, and secondary data analysis, to investigate how environmental variables influence migration patterns in vulnerable places such as coastal areas and riverine islands (chars). The findings show that climate-induced migration is the consequence of both acute environmental hazards and long-term socioeconomic vulnerabilities worsened by climate change. The study emphasizes the importance of government policy, local governance, and community resilience in affecting migration outcomes. This study contributes to a better understanding of the complex interplay between climate change, displacement, and migration in Bangladesh, allowing policymakers to devise more effective solutions to address the difficulties faced by climate-induced migration. The study emphasizes the importance of targeted interventions to improve adaptive ability and resilience in impacted communities, assuring long-term development in the face of continuous climatic problems.